2022
DOI: 10.22201/ib.20078706e.2022.93.4047
|View full text |Cite
|
Sign up to set email alerts
|

Variación estacional y nictémera en la distribución de Beloniformes (Pisces) en la boca de una laguna costera tropical

Abstract: El objetivo del estudio es analizar los patrones temporales en la distribución de Beloniformes en un estuario intermitente tropical. Durante 19 meses se realizaron muestreos en ciclos de 24 h cada mes, tomando muestras cada 2 horas (442 muestreos en total). Simultáneamente, se registraron in situ variables abióticas y bióticas, así como variables con registros histórico-regionales. Se capturaron 6 especies, de las cuales Strongylura notata notata mostró un pulso significativo en mayo-agosto, mientras que S. ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…This is due to the dominance of D. rhombeus and C. aguadulce in low salinity areas, in addition to other species with intermediate abundance such as D. auratus, E. melanopterus, E. plumieri and C. spilopterus, which together incorporate greater biomass to the environment of fluvial influence. In studies carried out in estuarine lagoon systems, a similar behavior has been observed in the abundance of fish species, indicating that salinity variations act as a "control" factor that determines the presence of dominant species (Barletta et al, 2008;Molina et al, 2020;Sosa-Lopez et al, 2007;Aguirre León et al, 2020;Castillo-Rivera & Morgado-Dueñas, 2022). The average weight was inverse to the previous indicators, in this case towards the environments with the highest salinity where species of greater size and weight with less abundance were recorded, such as H. sabinus, A. felis and several species of the Centropomidae family that use them depending on the biological stages that return to the system.…”
Section: Discussionmentioning
confidence: 62%
“…This is due to the dominance of D. rhombeus and C. aguadulce in low salinity areas, in addition to other species with intermediate abundance such as D. auratus, E. melanopterus, E. plumieri and C. spilopterus, which together incorporate greater biomass to the environment of fluvial influence. In studies carried out in estuarine lagoon systems, a similar behavior has been observed in the abundance of fish species, indicating that salinity variations act as a "control" factor that determines the presence of dominant species (Barletta et al, 2008;Molina et al, 2020;Sosa-Lopez et al, 2007;Aguirre León et al, 2020;Castillo-Rivera & Morgado-Dueñas, 2022). The average weight was inverse to the previous indicators, in this case towards the environments with the highest salinity where species of greater size and weight with less abundance were recorded, such as H. sabinus, A. felis and several species of the Centropomidae family that use them depending on the biological stages that return to the system.…”
Section: Discussionmentioning
confidence: 62%